Sentinel service technology in aquatic ecotoxicology through bioecotoximonitors - Argota-Pérez, George (2025)
Aquatic ecosystems are under continuous pressure from industrial, agricultural, and urban contaminants that form complex mixtures, making their evaluation highly challenging. Traditional chemical analyses perform an essential role but fail to accurately represent the real impact of these substances on biota. In this context, the bioecotoximonitor—defined as a fish with physiological and behavioral sensitivity to pollutants and associated with an indicator organism represents an innovation in aquatic ecotoxicology. The proposal focuses on a service-oriented technology that provides standardized environmental monitoring bioassays. This service includes breeding and maintenance protocols, exposure tests under laboratory or field conditions, recording of physiological and behavioral variables, and the issuance of reports with scientific and regulatory value. The main strength of the bioecotoximonitor lies in its ability to detect sublethal effects and behavioral alterations that precede ecological deterioration. Compared to conventional methods, it offers a comprehensive and sensitive perspective on the combined action of pollutants. Its technological foundation is supported by ecotoxicology, animal physiology, and behavioral biology, ensuring relevance and reproducibility. Thus, the bioecotoximonitor, as a sentinel organism, strengthens water management, ecotoxicological monitoring, and the integration of knowledge among academic, regulatory, and industrial sectors.